Incidence and mortality of pertussis disease in infants <12 months of age following introduction of pertussis maternal universal mass vaccination in Bogotá, Colombia (2020)
Background Maternal immunization with tetanus, diphtheria, and acellular pertussis (Tdap) vaccine confers protection to young infants. We aimed to describe trends in pertussis incidence and associated mortality in children aged <12 months before and after introduction of maternal Tdap immunization in Bogotá, Colombia. Methods Data on pertussis-related cases/deaths in infants aged <12 months were collected from SIVIGILA for the period 2005–2016, and compared incidence for the pre-vaccine introduction (2005–2012) and post-maternal Tdap vaccination (2014–2016) periods in infants aged <12 months and in three distinct age-strata; ≤6 weeks, 7–<28 weeks, and 28–52 weeks. Mortality comparisons were performed in all infants <12 months. Results From 2005 to 2016, 2315 laboratory or clinically-confirmed pertussis cases were reported in infants <12 months of age (278 cases in young infants aged ≤6 weeks); 55 pertussis deaths were reported in children aged <12 months. No pertussis deaths were reported in the 2014–2016 period. Since maternal Tdap introduction in 2013, a consistent decline in pertussis incidence and mortality was observed. In the time-series analysis, incidence declined from 209.4/100,000 persons (2005–2012) to 49.1/100,000 persons (2014–2016) in all children <12 months; a 87.5% (95%CI: 77.2-93.2%) reduction. For these same period’s incidence in young infants ≤6 weeks declined from 196.7 to 89.6/100,000 person-years (an 54.4% [95% CI: 35.4–67.9%] reduction). Greater incidence reductions were observed in older infants; 73.4% (95% CI: 68.4–77.6%) in those aged 7–<28 weeks, and 100% in those aged 28–52 weeks. A 100% reduction in Pertussis mortality in infants <12 months was observed. Since Tdap introduction, maternal vaccine coverage rose from <60% in 2013–2015 to 80% in 2016. Conclusions Implementation of maternal immunization in Bogotá may have contributed to the reduction in pertussis incidence and mortality among infants <12 months of age (ClinicalTrials.gov: NCT02569879).